Integrated review of management of hypertension by lifestyle changes, yoga, exercise, acupressure, plant/herbal and allopathic medications and newer interventions. - PA, Balaji; RV, Smitha (Indian Journal of Integrative Medicine, 2023)
Hypertension is a global epidemic with prevalence almost similar in urban and rural populations and it is a significant modifiable risk factor for cardiovascular disease, stroke, and renal diseases. Although many modalities of treatment are available, a large percentage of patients don’t have their blood pressure (BP) under control, hence, the management of hypertension has become a vital issue. We do find very few integrative reviews considering all feasible modalities of treatment for hypertension like lifestyle changes (low sodium intake, diet, reduction of bodyweight, limitations of alcohol consumption and cessation of smoking), yoga, exercise, acupressure, plant/herbal and allopathic medications and newer interventions, therefore, we performed a Medline search to review relevant articles in English literature. Data were constructed and issues were reviewed and we found that all the above modalities of treatment have reasonable scientific evidence and suggest to be used judiciously as monotherapy or in compatible adjunct combinations for better control of hypertension. We recommend more integrated treatment approaches and reviews in future. Key words: Hypertension, lifestyle changes, yoga, acupressure, herbal medicine.